Comparative study of conventional physiotherapy, electromyography (emg) biofeedback and isokinetic exercise intervention in person suffering osteoarthritis of knee - Amrizal, Faridahidayu (Universiti Sains Malaysia, 2016)
The present study was undertaken with an objective to To compare the effectiveness of conventional physiotherapy, electromyography (EMG) biofeedback and isokinetic exercise intervention on person suffering osteoarthritis (OA) of knee. Twenty eight cases on osteoarthritis of knee from Hospital Universiti Sains Malaysia (HUSM) in the age above 50 years old are involved. All cases involved then assessed with Western Ontario And Mcmaster Universities Arthritis Index (WOMAC) questionnaire, peak torque using Biodex 4 Isokinetic machine, Standing force and knee joint force using Force Platform And 3Dimensional (3D) Qualisys Track Manager software and muscle activation using electromyoghaphy (EMG). These assessments were done for the screening test and preintervention base line information. Thereafter they were randomly and equally categorized into three groups, viz. - Group A (N=9)- consist of control group received conventional physiotherapy exercise intervention; Group B (N=9) — received electromyography (EMG) biofeedback exercise intervention and Group C (N=10) — received isokinetic exercise intervention. Group wise respective intervention trainings were imparted for 20 sessions (45- 60 min.s /day; 2 days/ week for 10 weeks). Post-term analyses on all of the variables assessed in the pre-intervention phase were done on all of the cases after the completion of 10 weeks of intervention. Findings of this present study clarified that, although all of the interventions had beneficial impacts, EMG biofeedback intervention was observed as most effective in enhancement of muscle potentiality, while conventional exercise also was observed as having satisfactory outcomes. Further to that, compared to other intervention techniques, EMG biofeedback was also observed as mostly suitable in modulating fatigability in the subjects while Isokinetic training also were observed to have slight improvement in fatigue management. EMG biofeedback was also observed to improve in peak torque; while Isokinetic intervention was not at all beneficial for improvement in peak torque.